Bioorganic components and compounds of petroleum series in bottom sediments in Lake Tus and Lake Chyornoye (Khakassia); Contemporary Problems of Ecology; Vol. 10, iss. 2 - Russkikh I. V. Irina Vladimirovna; Strelnikova E. B. Evgeniya; Serebrennikova O. V. Olga Viktorovna; Elchaninova (El'chaninova) E. A. Elena Aleksandrovna (2017, 2017)
Title screen